Effects of a Home‐based Exercise Program on Anxiety and Mood Disturbances in Older Adults with Cancer Receiving Chemotherapy. Issue 5 (29th April 2019) - Loh, Kah Poh; Kleckner, Ian R.; Lin, Po‐Ju; Mohile, Supriya G.; Canin, Beverly E.; Flannery, Marie A.; Fung, Chunkit; Dunne, Richard F.; Bautista, Javier; Culakova, Eva; Kleckner, Amber S.; Peppone, Luke J.; et al.
Abstract : BACKGROUND/OBJECTIVE: Exercise interventions improve anxiety and mood disturbances in patients with cancer. However, studies are limited in older adults with cancer. We assessed the effects of exercise on anxiety, mood, and social and emotional well‐being in older patients with cancer during their first 6 weeks of chemotherapy. DESIGN: Exploratory secondary analysis of a randomized controlled trial (RCT). SETTING: Community oncology practices. PARTICIPANTS: Older patients (aged 60 years or older) undergoing chemotherapy (N = 252). INTERVENTION: Patients were randomized to Exercise for Cancer Patients (EXCAP) or usual care (control) for the first 6 weeks of chemotherapy. EXCAP is a home‐based, low‐ to moderate‐intensity progressive walking and resistance training program. MEASUREMENTS: Analysis of covariance, with study arm as the factor, baseline value as the covariate, and study arm × baseline interaction, was used to evaluate arm effects on postintervention anxiety (State Trait Anxiety Inventory [STAI]), mood (Profile of Mood States [POMS]), and social and emotional well‐being (Functional Assessment of Cancer Therapy–General subscales) after 6 weeks. RESULTS: Median age was 67 years; 77% had breast cancer. Statistically significant group differences were observed in the STAI score ( P = .001), POMS score ( P = .022), social well‐being ( P = .002), and emotional well‐being ( P = .048). For each outcome, EXCAP patients with worse baseline scores had larger improvements at 6 weeks; these improvements were clinically significant for STAI score and social well‐being. CONCLUSIONS: Among older cancer patients receiving chemotherapy, a 6‐week structured exercise program improved anxiety and mood, especially among those participants with worse baseline symptoms. Additional RCTs are needed to confirm these findings and evaluate the appropriate exercise prescription for managing anxiety, mood, and well‐being in this patient population. J Am Geriatr Soc 67:1005–1011, 2019.